Нові місцезнаходження рідкісних видів флори Придніпровської височини - Мельник, В.І.; Шиндер, О.І.; Діденко, С.Я. (Український ботанічний журнал, 2010)
Приведены новые местонахождения пяти редких видов флоры Украины на Приднепровской возвышенности: Crocus reticulatus Stev. ex Adams, Listera ovata (L.) R. Br., Stipa capillata L., Arum besserianum Schott и Corydalis marschalliana (Pall. ex Willd.) Pers. Описаны ценотические условия местообитаний этих видов в новых локалитетах. New locations of five species rare for the flora of Ukraine, Crocus reticulatus Stev. ex Adams, Listera ovata (L.) R. Br., Stipa capillata L., Arum besserianum Schott, and Corydalis marschalliana (Pall. ex Willd.) Pers., are recorded on the Dnieper Upland. Coenotic conditions of the species habitats in the new localities are described.